The problems in the application of the procedural separation. Principle of alternative determination: scope of article 285-A of the Code of Criminal Procedures - Escobar Antezano, Carlos (2009)
The determination of a punishable event is limited only to a factual description since an accusation has no power to determine the legal determination of a claim, that is why the inclusion of an event within a typical figure included in the complaint or indictment of the Government Attorney General’s Office may be modified at the time of issuing an order to open an investigation, an order of prosecution and a convicting sentence by virtue of the dissociation thesis, provided that requirements of homogeneity of the protected legal right, immutability of the events and evidence, preservation of the right to defense and coherence between factual and regulatory elements are met